Laser induced phase transition in epitaxial FeRh layers studied by pump-probe valence band photoemission - Pressacco, Federico; Uhlíř, Vojtěch; Gatti, Matteo; Nicolaou, Alessandro; Bendounan, Azzedine; Arregi, Jon Ander; Patel, Sheena K K; Fullerton, Eric E; Krizmancic, Damjan; Sirotti, Fausto (Structural dynamics (Melville, N.Y.), 2018)
We use time-resolved X-ray photoelectron spectroscopy to probe the electronic and magnetization dynamics in FeRh films after ultrafast laser excitations. We present experimental and theoretical results which investigate the electronic structure of FeRh during the first-order phase transition, identifying a clear signature of the magnetic phase. We find that a spin polarized feature at the Fermi edge is a fingerprint of the magnetic status of the system that is independent of the long-range ferromagnetic alignment of the magnetic domains. We use this feature to follow the phase transition induced by a laser pulse in a pump-probe experiment and find that the magnetic transition occurs in less than 50 ps and reaches its maximum in 100 ps.